Collagen fibril abnormalities in human and mice abdominal aortic aneurysm. (1st July 2020) - Jones, Blain; Tonniges, Jeffrey R.; Debski, Anna; Albert, Benjamin; Yeung, David A.; Gadde, Nikhit; Mahajan, Advitiya; Sharma, Neekun; Calomeni, Edward P.; Go, Michael R.; Hans, Chetan P.; Agarwal, Gunjan
ABSTRACT: Vascular diseases like abdominal aortic aneurysms (AAA) are characterized by a drastic remodeling of the vessel wall, accompanied with changes in the elastin and collagen content. At the macromolecular level, the elastin fibers in AAA have been reported to undergo significant structural alterations. While the undulations (waviness) of the collagen fibers is also reduced in AAA, very little is understood about changes in the collagen fibril at the sub-fiber level in AAA as well as in other vascular pathologies. In this study we investigated structural changes in collagen fibrils in human AAA tissue extracted at the time of vascular surgery and in aorta extracted from angiotensin II (AngII) infused ApoE −/− mouse model of AAA. Collagen fibril structure was examined using transmission electron microscopy and atomic force microscopy. Images were analyzed to ascertain length and depth of D-periodicity, fibril diameter and fibril curvature. Abnormal collagen fibrils with compromised D-periodic banding were observed in the excised human tissue and in remodeled regions of AAA in AngII infused mice. These abnormal fibrils were characterized by statistically significant reduction in depths of D-periods and an increased curvature of collagen fibrils. These features were more pronounced in human AAA as compared to murine samples. Thoracic aorta from Ang II-infused mice, abdominal aorta from saline-infused mice, and abdominal aorta from non-AAA human controls did not contain abnormal collagen fibrils. The structural alterations in abnormal collagen fibrils appear similar to those reported for collagen fibrils subjected to mechanical overload or chronic inflammation in other tissues. Detection of abnormal collagen could be utilized to better understand the functional properties of the underlying extracellular matrix in vascular as well as other pathologies. Statement of Significance: Several vascular diseases including abdominal aortic aneurysm (AAA) are characterized by extensive remodeling in the vessel wall. Although structural alterations in elastin fibers are well characterized in vascular diseases, very little is known about the collagen fibril structure in these diseases. We report here a comprehensive ultrastructural evaluation of the collagen fibrils in AAA, using high-resolution microscopy techniques like transmission electron microscopy (TEM) and atomic force microscopy (AFM). We elucidate how abnormal collagen fibrils with compromised D-periodicity and increased fibril curvature are present in the vascular tissue in both clinical AAA as well as in murine models. We discuss how these abnormal collagen fibrils are likely a consequence of mechanical overload accompanying AAA and could impact the functional properties of the underlying tissue. Graphical abstract: Image, graphical abstract